Iron in Cardiovascular Disease: Challenges and Potentials - Li, Shizhen; Zhang, Xiangyu (Frontiers in Cardiovascular Medicine, 2021)
Iron is essential for many biological processes. Inadequate or excess amount of body iron can result in various pathological consequences. The pathological roles of iron in cardiovascular disease (CVD) have been intensively studied for decades. Convincing data demonstrated a detrimental effect of iron deficiency in patients with heart failure and pulmonary arterial hypertension, but it remains unclear for the pathological roles of iron in other cardiovascular disease. Meanwhile, ferroptosis is an iron-dependent cell death that is distinct from apoptosis, necroptosis, and other types of cell death. Ferroptosis has been reported in several CVDs, including cardiomyopathy, atherosclerotic cardiovascular disease, and myocardial ischemia/reperfusion injury. Iron chelation therapy seems to be an available strategy to ameliorate iron overload-related disorders. It is still a challenge to accurately clarify the pathological roles of iron in CVD and search for effective medical intervention. In this review, we aim to summarize the pathological roles of iron in CVD, and especially highlight the potential mechanism of ferroptosis in these diseases.